Ab Initio Molecular–Dynamics Study of Structural and Bonding Properties of Liquid Fe–Light–Element–O Systems Under High Pressure - Ohmura, Satoshi; Shimojo, Fuyuki; Tsuchiya, Taku (Frontiers in Earth Science, 2022)
The structural and bonding properties of liquid iron–light–element–oxygen ternary systems such as Fe–H–O, Fe–C–O, Fe–Si–O, and Fe–S–O under high pressure are studied by ab initio molecular dynamics simulations. H, C, O, Si, and S are the candidate light elements in the Earth’s outer core (liquid iron is a major constituent). From our simulations, it is found that H, C, and O show “interstitial” type behavior while Si and S show “substitutional” type behavior in the liquid iron–light–element–O ternary systems. For the interactions between light elements, C–C, Si–Si, and Si–O show covalent–like interactions even under high–pressure condition. The Si–O covalent bond causes a shift in the ionic charge of Si to more positive, which could be related to the immiscibility of liquid Fe–Si–O.